Effect of coupling agent on crystallization and rheological properties of poly(ethylene terephthalate) composite masterbatches. Issue 11 (28th September 2015) - Jiang, Zhaohui; Guo, Zengge; Pu, Congcong; Jia, Zhao; Xiao, Changfa; Jin, Jian
Abstract : Poly(ethylene terephthalate)/carbon black/coupling agent composite masterbatches were fabricated using separate feeding technique. The effect of coupling agent on crystallization of composite masterbatches was investigated by differential scanning calorimetry, wide‐angle X‐ray diffraction, and Fourier transform‐infrared spectroscopy, respectively. The results show that the strong interfacial interaction among poly(ethylene terephthalate) (PET), coupling agent and carbon black hinders chains mobility in process of PET crystallization, which is illustrated by interfical structure model. Whereas, the crystallinity of composite masterbatch increases due to uniform dispersion of carbon black modified by coupling agent. Activation energy of viscous flow of the composite masterbatches is closer to that of virgin PET, so the spinning parameters can be controlled according to each other. Besides, structural viscosity index of composite masterbatches is greater due to strong interfacial interaction among PET, coupling agent and carbon black. Thus, in order to smooth spinning, the composite masterbatches need greater shear rate compared with PET/carbon black masterbatch. POLYM. COMPOS., 38:2358–2367, 2017. © 2015 Society of Plastics Engineers